Proceso de atención nutricional en paciente femenino de 47 años de edad con obesidad grado l y diabetes mellitus 2. - Pacheco Coello, Kennyi Madeleine (2022)
Diabetes mellitus type II is a pathology that goes hand in hand with obesity and seriously affects Ecuador, being the third cause of death in the country, an indicator that should cause the population to have a better quality of food to obtain a healthy life. And avoid suffering from this disease. The patient is a 47-year-old female who weighs 71 kg and is 1.50 meters tall. She was assessed with anthropometric measurements and indicated a nutritional diagnosis of obesity grade l since his body mass index is 31 kg/m2. The patient was diagnosed with Type 2 Diabetes Mellitus 7 years ago. He went to the Martin Icaza General Hospital to the emergency area because he presented signs and symptoms of paleness, blindness, and fainting that characterizes him as Dizziness. For which he refers that he does not have an established or indicated treatment to control his pathology, in terms of relevant biochemical tests, his glycosylated hemoglobin values are outside normal parameters, which reveals that the patient has uncontrolled diabetes.